Worldview of Tribal Communities in Pachmarhi Biosphere Reserve of India - Chandra Prakash Kala (Global Journal of Ecology - Peertechz Publications, 2017)
Tribal communities living in the far flung areas, including forests and forest fringes, derive a set of inferences and assumptions about the world around them, over the years. The present study, therefore,aims to document such worldview of tribal communities living in the Pachmarhi Biosphere Reserve of India. The questionnaire surveys and interviews were conducted in the villages dominated by tribal communities and information on their worldview was gathered. Two dominant tribal groups such as Gond and Korku were identified in the study area. The social organization of Gond and Korku reveals hat they are divided into clans. They have developed various stories about the natural resources, ecosystem, environment and environmental phenomenon. The younger generations though generally disagree with worshipping totemic objects, the taboo attached to them are still respected. The tribal people collect medicinal plants for therapy as per the customary norms, and there are only limited days which they consider auspicious for such collection from the wild. Mahua (Madhuca indica) is one of the important plant species which is used for multiple purposes, including prediction of weather and agriculture yields. The Korku tribe broadcasts and sows the seeds as per the position of rainbow during rainfall; if the rainbow is in the east of the village it is considered good to broadcast seeds for their good growth. The worldview of tribal communities is based on the nature, its resources and functions accordingly the present study describes such naturalistic worldview of tribes.